Do Productive Uses of ICT Connect to Income Benefits: A Case Study on Teleuse@BOP4 Survey in Indonesia - Ibrahim Kholilul Rohman (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2013)
The question whether the telecommunication sector has been really supporting poverty alleviation and increasing welfare at the household level, in terms of an additional income in Indonesia is still undisclosed. This paper aims at investigating whether the mobile phone access and the uses on productive features/content/services have brought many benefits to the households in terms of an additional income based on the BOP survey conducted by LIRNEAsia and the Institute for Economic and Social Research, University of Indonesia (LPEM FEUI) in 2011. The paper found that the respondents with the productive use to their device have a higher likelihood for contributing to their household income.